The IMPROVING STUDENT LEARNING OUTCOMES THROUGH DISCOVERY LEARNING MODEL IN SCIENCE SUBJECTS ELECTRICITY AND ELECTRICAL TECHNOLOGY IN THE ENVIRONMENT OF CLASS IX SMP NEGERI 1 KUNIR LESSON YEAR 2021/2022 ODD SEMESTER - Edy Suwarno (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2023)
This study aimed to improve the learning outcomes of 9th grade students of SMPN 1 Kunir in following the science learning of electricity and electrical technology with a discovery learning approach. This research took place at SMPN 1 Kunir, Kunir District, Lumajang Regency, East Java Province. This research was conducted in the odd semester of the 2021 - 2022 school year from September to October 2021. The research subjects were students of Class IX SMPN 1 Kunir in the 2021/2022 academic year on science learning on the subject of electricity and electrical technology consisting of 32 students. Based on the results of the research conducted, it can be concluded that the application of discovery learning by teachers is considered to be able to improve student learning outcomes in learning electricity and electrical technology in the environment in class IX SMPN 1 Kunir. This can be seen through the results of observations and assessments made by teachers on student learning outcomes increased significantly starting from the pre-cycle with average results less increased to quite good in cycle I and became good in cycle II. So, it can be concluded that the implementation of the action of applying the Discovery learning type learning model in learning science electricity and electrical technology in class IX SMPN 1 Kunir can improve student learning outcomes in the classroom.